Pregnancy in porphyria and its complications: a case report - Mital, Tuhina K.; Fuke, Rujuta P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
As with many rare diseases, little is known about the porphyrias and reproduction. Knowledge pertaining to complications in pregnancy in a patient with porphyria is even more scant. The information which we have is from attending on individual cases. The following case report demonstrates a rare case of porphyria cutanea tarda in a 30 year old female patient, diagnosed around pubertal age, who presented to the Emergency department as a case of severe anemia who had delivered a still born baby the same day. Still births along with spontaneous abortions, preeclampsia and low birth weights are few of the known complications of pregnancy in patients with porphyria.